Composite material prepared using recycled abs and injection molding method thereof
Patent Information
- Application Number
- CN202611334779.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-27
AI Technical Summary
[0010]本发明要解决的技术问题是:克服现有回收ABS材料韧性差、流动性过高、尺寸稳定性差、注塑成型良品率低的缺陷,提供一种利用回收ABS制备的复合材料及其注塑成型方法
[0027]本发明通过“增韧剂+扩链剂+增强填料+纳米填料+相容剂”五组分协同改性,系统性地解决回收ABS的多重性能缺陷。其中,ABS高胶粉用于提高橡胶相含量,补偿老化损失的冲击韧性;扩链剂与ABS分子链端的羧基/羟基反应,重新连接断裂分子链,降低MFR;短切玻纤用于提高拉伸强度和弯曲模量,抵消增韧带来的刚性损失;纳米碳酸钙用于提高尺寸稳定性,降低注塑成型收缩率;ABS-g-MAH用于改善玻纤与ABS基体的界面结合,促进扩链反应。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of waste plastic recycling technology, specifically to a composite material prepared from recycled ABS and its injection molding method. Background Technology
[0002] ABS (acrylonitrile-butadiene-styrene copolymer) is widely used in electronics, automobiles, and home appliances due to its excellent mechanical properties, processing performance, and surface gloss. However, a large number of ABS products become waste after use, putting enormous pressure on the environment. Recycling ABS is an important way to achieve a circular economy in plastics.
[0003] However, waste ABS will undergo thermo-oxidative aging during use and recycling, leading to the following problems: (1) The PB rubber phase cross-links or degrades, which significantly reduces the toughness of the material, and the impact strength is only 40%-60% of that of virgin ABS; (2) The molecular chains of the ABS matrix break, the melt flow rate increases, and overfilling and flash are likely to occur during injection molding; (3) The material often contains label residue, oil stains, and other plastic impurities, which affect the appearance and mechanical properties of the product.
[0004] Several technical solutions have been proposed to improve the performance of recycled ABS. For example, Chinese patent application CN120441989A discloses a composite material based on recycled ABS, comprising 100 parts waste ABS plastic, 2-5 parts bifunctional macromolecular chain extenders, 3-8 parts functionalized nanofillers, and other additives. This technology only involves the combination of chain extenders and nanofillers, without systematically considering the synergistic effects of toughening, reinforcement, and dimensional stability. Other technical solutions use macromolecular chain extenders to regenerate and modify ABS waste to improve its anti-aging and mechanical properties. However, these technologies focus on the single dimension of molecular chain repair and lack effective means to compensate for the toughness loss caused by the aging of the rubber phase in recycled ABS.
[0005] In terms of toughening modification, existing technologies mainly use toughening agents such as SBS, ABS high-resin powder, K resin, and TPU to improve the impact strength of recycled ABS plastics. For example, Chinese patent CN112143163A discloses a method of toughening and modifying recycled ABS by adding ABS high-resin powder and silane coupling agents, which improves tensile strength, elongation at break, and impact resistance. However, simple toughening often leads to a decrease in material rigidity and heat resistance, making it difficult to meet the needs of high-end applications. Although the recycled ABS modified material proposed by China Petroleum & Chemical Corporation can significantly improve toughness, it mainly focuses on the single property of toughening.
[0006] Regarding reinforcement and modification, existing technologies have attempted to strengthen recycled ABS materials by adding glass fibers. For example, Chinese patent application CN119859375A discloses a composite material made from recycled ABS, comprising 25-30 parts recycled ABS, 15-20 parts high-density polyethylene, and 4-8 parts glass fibers, modified by melt blending of unsaturated anhydride, unsaturated rubber, and an initiator. Another example is Chinese patent CN115895173A, which discloses an economical, cold-resistant, low-odor glass fiber reinforced composite material. This material utilizes the properties of non-crystalline recycled copolyester and R-ABS resin, introducing a molecular chain extender to link the recycled polyester, thereby restoring the material's properties. Other patents use waste glass fiber as a reinforcing agent to prepare ABS / HIPS plastic alloy materials, improving interfacial bonding by adding ABS-g-MAH as a compatibilizer. However, while glass fiber reinforcement increases rigidity, it often leads to a decrease in material toughness, and due to the presence of impurities in recycled ABS, the interfacial bonding between the glass fiber and the matrix resin is difficult to guarantee.
[0007] In the field of nanofiller modification, nano-calcium carbonate has been used in the modification of ABS and its recycled materials. Studies have shown that nano-calcium carbonate can be used as a reinforcing agent and nucleating agent, improving the mechanical properties and processing flowability of materials while maintaining toughness. For example, Chinese patent CN105713335A discloses a nano-modified high-impact ABS composite plastic, achieving the dual effects of toughening and reinforcement through nanoparticles. However, single nanofiller modification is difficult to simultaneously solve the multiple problems of high flowability, poor dimensional stability, and insufficient interfacial compatibility of recycled ABS.
[0008] In terms of compatibilizer design, existing technologies involve grafting and modifying recycled ABS materials to prepare compatibilizers for use in polymer blends and polymer / filler composites. For example, Chinese patent application CN120061037A discloses a SAG-g-rABS compatibilizer-modified rABS / rHIPS blend and its preparation method, which improves the compatibility of recycled ABS with other plastic blends by using a self-made compatibilizer. However, this type of technology mainly addresses the interface problem when blending dissimilar plastics, and lacks systematic research on the synergistic modification of multi-components in a single recycled ABS system.
[0009] Current research on the modification of recycled ABS mainly focuses on single-component or two-component modification, lacking systematic technical solutions for improving multiple properties. Furthermore, existing technologies are insufficiently integrated with injection molding processes, failing to systematically consider the requirements of recycled ABS materials in injection molding regarding flowability, shrinkage, and product appearance. This results in poor molding stability and low yield rates in actual injection molding production of modified recycled ABS. Therefore, developing a composite material and its injection molding method that can systematically improve the mechanical properties, processing performance, and dimensional stability of recycled ABS is a pressing technical problem to be solved in the field of high-value utilization of recycled ABS. Summary of the Invention
[0010] The technical problem to be solved by the present invention is to overcome the defects of existing recycled ABS materials, such as poor toughness, excessive fluidity, poor dimensional stability, and low injection molding yield, and to provide a composite material prepared by recycled ABS and its injection molding method.
[0011] This invention discloses a composite material prepared using recycled ABS, which is composed of the following components in parts by weight:
[0012] 100 parts recycled ABS resin; 5-20 parts toughening agent; 0.5-3 parts chain extender; 10-30 parts reinforcing filler; 2-8 parts nano filler; 2-6 parts compatibilizer.
[0013] The recycled ABS resin undergoes the following pretreatment before use:
[0014] Crushing: Crushing waste ABS products into flakes or granules of 5-15mm;
[0015] Magnetic separation / air separation: removes physical impurities such as metal, labels, and dust;
[0016] Cleaning: Use alkaline cleaning solution or deionized water to clean and remove oil and surface contaminants;
[0017] Drying: Dry at 80-100℃ for 4-8 hours, controlling the moisture content to ≤0.1%.
[0018] After the above pretreatment, the melt flow rate (220℃ / 10kg) of the recycled ABS resin was 15-35 g / 10min, and the notched impact strength of the cantilever beam was 8-15 kJ / m. 2 .
[0019] Preferably, the toughening agent is ABS high-resin powder and / or POE-g-MAH, the chain extender is an epoxy chain extender or an anhydride chain extender, the reinforcing filler is chopped glass fiber, the nanofiller is nano-calcium carbonate and / or nano-silica, and the compatibilizer is ABS-g-MAH.
[0020] Based on the above technical solution, the toughening agent is 8-12 parts of ABS high-resin powder, the chain extender is 1-2 parts of ADR, the reinforcing filler is 15-25 parts of chopped glass fiber, the nano filler is 3-5 parts of nano calcium carbonate, and the compatibilizer is 3-5 parts of ABS-g-MAH.
[0021] The above-mentioned composite material prepared using recycled ABS is prepared by injection molding, which includes the following steps:
[0022] Step 1: The recycled ABS resin is pre-treated by crushing, washing, and drying.
[0023] Step 2: Weigh out the pretreated recycled ABS resin, toughening agent, chain extender, nanofiller, and compatibilizer according to the formula, and mix them evenly;
[0024] Step 3: The mixture from Step 2 and the reinforcing filler are separately fed into a twin-screw extruder for melt blending, extrusion granulation, and extrusion. The extruder processing temperatures are: Zone 1 180-200℃, Zone 2 200-220℃, Zone 3 220-235℃, Zone 4 230-240℃, Zone 5 230-240℃, and the die head temperature is 220-230℃. The screw speed is 200-400 rpm.
[0025] Step 4: The granules obtained in Step 3 are injection molded to obtain ABS composite material products. The injection molding process parameters are: barrel temperature 200-230℃, mold temperature 60-80℃, injection pressure 60-100 MPa, holding pressure 40-70 MPa, and cooling time 20-40 seconds.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] This invention systematically addresses multiple performance defects of recycled ABS through a five-component synergistic modification process involving toughening agent, chain extender, reinforcing filler, nanofiller, and compatibilizer. Specifically, high-rubber ABS powder increases the rubber phase content, compensating for impact toughness losses due to aging; the chain extender reacts with the carboxyl / hydroxyl groups at the ends of the ABS molecular chains, reconnecting broken molecular chains and reducing molecular weight ratio (MFR); chopped glass fiber improves tensile strength and flexural modulus, offsetting the rigidity loss caused by toughening; nano-calcium carbonate improves dimensional stability and reduces injection molding shrinkage; and ABS-g-MAH improves the interfacial bonding between glass fiber and the ABS matrix, promoting the chain extension reaction.
[0028] This invention simultaneously improves toughness, strength, processing fluidity, and dimensional stability, overcoming the limitations of traditional modification technologies with their single function. Specifically, it achieves a synergistic balance between toughening and reinforcement: high-rubber powder compensates for rubber phase loss, while glass fiber and nanofillers compensate for rigidity loss, resolving the contradiction between toughening agents reducing rigidity and reinforcing fillers reducing toughness. Chain extension repair effectively reduces melt flowability, lowering the melt flow rate (MFR) from 28.5 g / 10min to 12.3 g / 10min, making the material more suitable for injection molding and reducing flash and overfilling. Dimensional stability is significantly improved; the filling and nucleation effects of nanofillers reduce injection shrinkage from 0.85% to 0.48%, significantly improving product warpage. Furthermore, compared to virgin ABS, the mechanical properties of the material obtained by this invention can reach 85-95% of virgin ABS, while reducing raw material costs by 40-60%, achieving high-value reuse of waste plastics. Detailed Implementation
[0029] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and do not limit the scope of the invention. The experimental materials, reagents, etc. used in the following embodiments can be obtained commercially or by known experimental methods.
[0030] Example 1
[0031] The formulation of the composite material is as follows:
[0032] Recycled ABS resin: 100 parts derived from waste electronic and electrical appliance casings, pre-treated by crushing, washing, and drying, with a moisture content of 0.08%, an MFR (220℃ / 10kg) of 28.5 g / 10min, and an impact strength of 12.3 kJ / m. 2 ;
[0033] ABS high-polymer powder: 10 parts;
[0034] ADR chain extender: 1.5 parts;
[0035] Short-cut glass fiber (4.5mm in length): 20 parts;
[0036] Nano-sized calcium carbonate (50nm particle size): 4 parts;
[0037] ABS-g-MAH compatibilizer: 4 parts.
[0038] The preparation steps are as follows:
[0039] Pretreated recycled ABS resin, high-resin powder, ADR, nano-calcium carbonate, and ABS-g-MAH were mixed for 5 minutes in a high-speed mixer. The mixture was fed into the main feed port of a twin-screw extruder, while chopped glass fibers were added from the side feed port. The extruder temperatures were as follows: Zone 1 190℃, Zone 2 210℃, Zone 3 225℃, Zone 4 235℃, Zone 5 235℃, Die head 225℃, and screw speed 300 rpm. The extruded strips were water-cooled, pelletized, and dried to obtain composite material granules.
[0040] The granules are injection molded on an injection molding machine. Process parameters: barrel temperature 220℃, mold temperature 70℃, injection pressure 80 MPa, holding pressure 55 MPa, cooling time 30 seconds.
[0041] Example 2
[0042] The difference from Example 1 is that: 8 parts of ABS high-resin powder, 1 part of ADR chain extender, 15 parts of chopped glass fiber, 3 parts of nano-calcium carbonate, and 3 parts of ABS-g-MAH. The preparation method is the same as in Example 1.
[0043] Example 3
[0044] The difference from Example 1 is that: 12 parts of ABS high-resin powder, 2 parts of ADR chain extender, 25 parts of chopped glass fiber, 5 parts of nano-calcium carbonate, and 5 parts of ABS-g-MAH. The preparation method is the same as in Example 1.
[0045] Comparative Example 1
[0046] The difference from Example 1 is that no ABS high-resin powder and ADR chain extender are added; that is, only recycled ABS resin + 20 parts glass fiber + 4 parts nano calcium carbonate + 4 parts ABS-g-MAH are used. The preparation method is the same as in Example 1.
[0047] Comparative Example 2
[0048] The difference from Example 1 is that chopped glass fibers and nano-calcium carbonate are not added; that is, only recycled ABS resin + 10 parts high-resin powder + 1.5 parts ADR chain extender + 4 parts ABS-g-MAH are used. The preparation method is the same as in Example 1.
[0049] Comparative Example 3
[0050] The difference from Example 1 is that no modifying agents are added; that is, pretreated recycled ABS resin is used directly for granulation and injection molding. The preparation method is the same as in Example 1.
[0051] Performance testing
[0052] 1. The performance of the samples from Examples 1-3 and Comparative Examples 1-3 was tested according to the following standards and methods:
[0053] 2. The test results are shown in the table below:
[0054] 3. Results Analysis
[0055] 3.1 The tensile strength (48.5 MPa) of Example 1 was 51% higher than that of Comparative Example 3 (unmodified recycled ABS, 32.1 MPa) and 15% higher than that of Comparative Example 1 (untoughened chain extender, 42.1 MPa); the impact strength (28.6 kJ / m) was... 2 Compared to Comparative Example 3, the efficiency was increased by 132%, compared to Comparative Example 2 (without reinforcing filler, 35.2 kJ / m³). 2 Although slightly lower, its overall mechanical properties are the best.
[0056] 3.2 The MFR decreased from 28.5 g / 10min in Comparative Example 3 to 12.3 g / 10min in Example 1, which is comparable to the MFR of native ABS (about 10-15 g / 10min), significantly improving processing flowability.
[0057] 3.3 The injection molding shrinkage rate decreased from 0.85% in Comparative Example 3 to 0.48% in Example 1, and the dimensional stability of the product was significantly improved.
[0058] 3.4 The comprehensive mechanical properties of Example 1 are close to those of virgin ABS (typical values for virgin ABS: tensile strength 45-50 MPa, impact strength 25-30 kJ / m). 2 However, the cost of raw materials has decreased by about 50%.
[0059] In summary, the composite material and injection molding method of this invention can be directly applied to existing plastic granulation and injection molding production lines without equipment modification. The composite material prepared by this invention can be widely used in automotive interior and exterior parts, household appliance housings, electronic appliance housings, daily plastic products, and other fields, and has significant industrial application value and environmental benefits.
[0060] The applicant declares that, based on the above embodiments, those skilled in the art can combine the specific content values of a certain component in the above embodiments with the technical solutions in the invention content section to generate new numerical ranges, which are also within the scope of this invention. To keep the specification concise, this application will not list these numerical ranges.
Claims
1. A composite material prepared using recycled ABS, characterized in that, It is made from the following components in parts by weight: 100 parts of recycled ABS resin; Toughening agent 5-20 parts; Chain extender 0.5-3 parts; 10-30 parts of reinforcing filler; 2-8 parts of nanofiller; Compatibilizer 2-6 parts.
2. The composite material according to claim 1, characterized in that, The recycled ABS resin is derived from waste electronic and electrical appliance casings, automotive interior and exterior parts, or daily plastic products. Before use, it undergoes crushing, washing, and drying pretreatment, with a moisture content of ≤0.1%.
3. The composite material according to claim 1, characterized in that, The melt flow rate of the recycled ABS resin is 15-35 g / 10min at 220℃ / 10kg, and the notched impact strength of the cantilever beam is 8-15 kJ / m. 2 .
4. The composite material according to claim 1, characterized in that, The toughening agent is ABS high-resin powder and / or POE-g-MAH, the chain extender is an epoxy chain extender or an anhydride chain extender, the reinforcing filler is chopped glass fiber, the nanofiller is nano calcium carbonate and / or nano silica, and the compatibilizer is ABS-g-MAH.
5. The composite material according to claim 4, characterized in that, The chopped glass fibers have a length of 3-6 mm, and the nanofiller has a particle size of 20-100 nm.
6. The composite material according to claim 1, characterized in that, The toughening agent is 8-12 parts of ABS high-resin powder, the chain extender is 1-2 parts of ADR, the reinforcing filler is 15-25 parts of chopped glass fiber, the nanofiller is 3-5 parts of nano calcium carbonate, and the compatibilizer is 3-5 parts of ABS-g-MAH.
7. The injection molding method for preparing the composite material according to any one of claims 1-6, characterized in that, Includes the following steps: Step 1: The recycled ABS resin is pre-treated by crushing, washing, and drying. Step 2: Weigh out the pretreated recycled ABS resin, toughening agent, chain extender, nanofiller, and compatibilizer according to the formula, and mix them evenly; Step 3: The mixture from Step 2 and the reinforcing filler are separately fed into a twin-screw extruder for melt blending, extrusion granulation; Step 4: The granules obtained in Step 3 are injection molded to obtain ABS composite material products.
8. The preparation method according to claim 7, characterized in that, In step three, the processing temperature of the twin-screw extruder is: zone 1 180-200℃, zone 2 200-220℃, zone 3 220-235℃, zone 4 230-240℃, zone 5 230-240℃, and the die head temperature is 220-230℃; the screw speed is 200-400 rpm.
9. The preparation method according to claim 7, characterized in that, In step four, the injection molding process parameters are: barrel temperature 200-230℃, mold temperature 60-80℃, injection pressure 60-100 MPa, holding pressure 40-70 MPa, and cooling time 20-40 seconds.
Citation Information
Patent Citations
Nano modified high-impact-resistance ABS composite plastic
CN105713335A
Toughening modification method of waste lead-acid storage battery shell ABS plastic
CN112143163A
Marine regenerated plastic modified ABS (Acrylonitrile Butadiene Styrene) alloy and preparation method thereof
CN115895173A
Recycled ABS modified material and preparation method thereof
CN119859375A
Composite material based on recycled ABS (Acrylonitrile Butadiene Styrene) plastic and preparation method thereof
CN120061037A